Implementation of Communication Strategies in Social Advertising Texts - M. V. Terskikh (Научный диалог, 2020)
The analysis of communicative strategies, tactics and techniques that are implemented in the texts of social advertising are presented in the article. The relevance of the study is determined by the fact that for social advertising, the issue of communicative effectiveness, which is closely related to the concept of communicative perspective and the choice of strategies and tactics that ensure the greatest effectiveness in achieving the goal, is significant and ambiguous. Particular attention is paid to the frustration strategy, which is aimed at creating psychological tension in order to remove the recipient from the so-called “comfort zone” through intimidation with a negative prognosis. The tactics and techniques that implement this strategy in the messages of both Russian and foreign outdoor social advertising are described in detail. This strategy from the author’s point of view is the basic (most frequent and most effective) for social advertising, the remaining selected strategies (management of criticality of perception, mnemonic, association and dissociation, etc.) are considered as additional, aimed at increasing the effectiveness of the frustration strategy. Since the influencing nature of social advertising is achieved, among other things, through the creolization of the text, special attention is paid to the verbal and visual implementation of the selected strategies, tactics and techniques.